From GHGs abatement potential to viable CDM projects: The case of Cambodia, Lao PDR and Vietnam - Dang Hanh; Axel Michaelowa; Friso de Jong (Hamburg Institute of International Economics (HWWA), 2006)
This study evaluates the CDM potential in Cambodia, Lao PDR and Vietnam by focusing not only on the absolute GHG abatement value of these countries. Rather, the potential of CDM inflows into the three countries will be identified through assessing the comparative CDM endowment on the basis of an holistic analysis of each country, thereby highlight the relative positions of Cambodia, Lao PDR, and Vietnam in the global CDM market. The three main factors determining the competitiveness of Cambodia, Laos and Vietnam in the global CDM market will be examined, namely Potential supply size - countries' facts, Country business climate and Country CDM institutions and CDM project experience. The study shows the overall competitiveness level of each studied country as well as discusses which activities a country shall take to maximise the opportunities to convert theoretical mitigation options into real CDM investments. In Vietnam, for instance, the highest challenge now is to make CDM ideas economically feasible. This study shows that it is questionable that a boom of CDM investment inflows into Vietnam or - in more quantitative word - a dozen of CDM projects will be registered before 2012. In Cambodia, the probability to get a couple of CDM projects running in the first commitment period is not high although the country is quite ahead in establishing their CDM institutions in comparison with other LDCs. One of the solutions to get through the narrow window is to gain attention from multilateral carbon funds, like the Community Development Carbon Fund (CDCF) and Bio Carbon Fund (BioCF). In the case of Lao PDR, this study demonstrates that the entry into the CDM is likely to be extremely high competitive for them given their poor CDM endowment and the lag behind activities of the government in constituting its own CDM structure. Thus, Laos needs to make a greater effort to develop its capacity to provide a basic sufficient framework to make the country as of one CDM-LDC destination in the international donors' eyes.
Keywords: 330